THE INFLUENCE OF INFORMATION QUALITY AND SERVICE QUALITY ON SATISFACTION OF SERVICE RECEIVING COMMUNITIES IN YOGYAKARTA RELIGIOUS COURT OFFICE - Rita Listiyanti; Anna Sulistyawati (ZILLZELL MEDIA PRIMA, 2023)
The objectives of this study include: (1) To determine the magnitude of the influence of the quality of information on the satisfaction of service recipients at the Yogyakarta Religious Court Office. (2) To determine the magnitude of the influence of service quality on the satisfaction of service recipients at the Yogyakarta Religious Court Office. (3) To determine the magnitude of the influence of information quality and service quality on the satisfaction of service recipients at the Yogyakarta Religious Court Office. This type of research was quantitative research. The population in this study were all service recipients at the Yogyakarta Religious Court Office. The sampling technique used simple random sampling technique with a total sample of 100 people. Data collection techniques in this study using a questionnaire. Data analysis technique using multiple regression analysis. Based on the findings and data analysis that has been carried out in the previous chapter, the following conclusions can be drawn: (1) The quality of information has a positive effect on the satisfaction of service recipients at the Yogyakarta Religious Court Office. (2) The quality of service has a positive effect on the satisfaction of the service recipient community at the Yogyakarta Religious Court Office. (3) The quality of information and service quality has a positive effect on the satisfaction of service recipients at the Yogyakarta Religious Court Office. Variable information quality and service quality affect community satisfaction by 30.9%, while the remaining 69.1% is influenced by other variables outside the research.